Library and Information Science Initiatives and Resources for Sustainable Development - Okoroma, F. N. (European Journal of Applied Sciences, 2023)
Library and information science remains the pivot that drives societal development. Advanced economies are reputable for access and utilization of huge quality hard information, as this is a driving force that triggers and sustains development at all levels. Though Library and Information Science (LIS) through their various activities and resources have been playing a key role towards enhancing sustainable development, yet the literature output of LIS scholars capturing sustainable development issues is relatively low when compared with the increasing importance of the subject in the scientific world. This work focuses on Library and information science activities and their resources as it relates to sustainable development. The paper brings to the limelight, the role of Library and Information science (LIS) activities and resources on sustainable development. Such roles include awareness/ advocacy programs towards achieving sustainable development goals. It showcases and maximizes access and impact of valuable literatures, which trigger societal advancement. Again the development of information literacy programme by LIS centers enhances both information access and utilization capacity of the general public and decision makers. This on the long run translates to wisdom and ideas that propel societal development. Others are Open Knowledge Foundation, Green library and the development of Institutional Repository, which is a crucial resource in the advancement and sustenance of the different arms of the society, including the political, judiciary, health sector, education, transportation, industries, power, commerce and infrastructure.